ChemInform Abstract: Catalytic, Asymmetric Halofunctionalization of Alkenes — A Critical Perspective. Issue 10 (7th March 2013) - Denmark, Scott E.; Kuester, William E.; Burk, Matthew T.
Abstract Review: about 100 refs.